STRATEGI LITERASI DIGITAL UNTUK MENGOPTIMALKAN TEKNOLOGI DALAM PENDIDIKAN - Syarifah Kurniawati; Isma Apriliana Putri Latifa; Moh. Syarief Hidayatullah; Siti Fadilah Elka Hidayati MS (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2024)
This research chose the topic of digital literacy because in today’s increasingly sophisticated era, everyone knows what digital is, especially students. This research method uses a method, namely literature review. This research also aims to train a person’s ability to apply this digital technology. The main strategy that can be carried out in optimizing digital is to provide information that can be accessed, especially for students, so that they better understand the functions of this technology. Digital literacy does not only include aspects of ability but also includes the development of their critical thinking in searching for various information. This research can be concluded that digital literacy is the responsibility of society, because this is useful for protecting all aspects of the privacy of their own personal data. The importance of digital literacy as a system requirement aims to be able to provide information technology in the future era.